Hospital admissions for hemolytic disease of the newborn in the state of Piaui, between 2014 and 2019 (Research, Society and Development, 2021)
Hemolytic Disease of the Fetus and Newborn (HDFN) is caused by maternal alloimmunization to erythrocyte antigens, in which fetal and neonatal erythrocytes are destroyed, leading to fetal hemolysis and other injuries that must be monitored by a multidisciplinary team, which demands expenses for the public health system. This study aimed to describe hospitalizations by HDFN in the state of Piauí in the period between 2014 and 2019. It is a qualitative and quantitative descriptive study that used secondary data to describe hospitalizations by HDFN, in the state of Piauí between the years 2014 to 2019 During the study period, there were a total of 70 admissions due to HDFN, which represents only 0.40% of admissions across the country in the same year. The average stay of these hospitalizations is 5.4 days, while the average cost is R$ 506.24. In Brazil, there were 64 deaths in relation to these admissions and the period in question, none of which occurred in Piauí. It is clear, then, that there is a need to carry out further studies on this topic to gain knowledge of the real nature of HDFN cases in the state of Piauí. It is not possible to infer whether there is underreporting of cases or if in fact there is a smaller number of occurrences. In addition, in 2018 there was a dissonant increase in the number of cases on the coast, and there are no records in the literature to help justify this increase.